Frankenstein in Baghdad: a Contemporary Iraqi Dystopian Writing - Al-Shammari, Zainab Abdulkadhim Salman (Al-Adab Journal, 2021)
The present essay is personal reading of Ahmed Saadawi’s novel Frankenstein in Baghdad, which is viewed in light of the development of the genre of utopian/dystopian writing not only in Western literature but also in the Arab/Islamic literature, highlighting the way the Iraqi writer understood the realities in his own country following the American invasion. The novel is a metaphor of the intertribal violence that is still shaking the illusory peace of the country, affecting the lives and destinies of a people which has not completely recovered from the horrors of the wars of the last decades. “Frankenstein in Baghdad… is something of an exorcism of the evil spirits of an era not quite past. Saadawi’s goal isn’t to resolve the horror of war, but rather to thrust the reader into its midst so that they may question its senselessness”. ~ Zahra Hankir